Juridical Analysis of Law Enforcement Against Lobster Seed Smuggling at Soekarno-Hatta International Airport, Tangerang - La Ode Sarifin; I Made Kantikha; Markoni Markoni; M. S. Anabertha Sembiring (Green Publisher Indonesia, 2025)
The smuggling of baby lobster seeds is a criminal act in the fisheries sector that not only causes economic losses to the state but also threatens the sustainability of marine ecosystems. This practice frequently occurs at the Soekarno Hatta International Airport, which is used as a strategic route by perpetrators to illegally export baby lobster seeds abroad. Law enforcement against baby lobster smuggling is crucial as it directly relates to the protection of fishery resources and the economic sustainability of coastal communities. The primary research questions of this study are about what factors contribute to lobster seed smuggling and how is law enforcement implemented in relation to Act 17 of 2006 on Customs. The objectives of this research are to analyze the causes of smuggling and evaluate the enforcement of relevant laws. This research employs normative and empirical juridical methods, with data collected through literature reviews and interviews with law enforcement officials involved in the process of law enforcement. The research results indicate that law enforcement efforts still face obstacles, including the high international demand for baby lobster exports, weak supervision systems, limited technology, and low legal awareness among the public. These conditions result in suboptimal law enforcement in practice, while penalties have not fully achieved a deterrent effect. In conclusion, although Indonesia has an adequate legal framework, its implementation remains reactive and has not addressed the root causes of the issue. To improve effectiveness, enhanced inter-agency coordination, strengthened supervision systems, and increased public legal awareness are necessary.